2019
DOI: 10.1097/ta.0000000000002563
|View full text |Cite
|
Sign up to set email alerts
|

Early single-dose treatment with exosomes provides neuroprotection and improves blood-brain barrier integrity in swine model of traumatic brain injury and hemorrhagic shock

Abstract: BACKGROUND Administration of human mesenchymal stem cell (MSC)–derived exosomes can enhance neurorestoration in models of traumatic brain injury (TBI) and hemorrhagic shock (HS). The impact of early treatment with MSC-derived exosomes on brain injury in a large animal model remains unknown. We sought to evaluate the impact of early single-dose exosome treatment on brain swelling and lesion size, blood-based cerebral biomarkers, and blood-brain barrier (BBB) integrity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…As an important component of paracrine signaling in stem cells, exosomes appear to be promising candidates for repairing tissue injury in place of stem cells (Lazar et al, 2018 ; Williams et al, 2020 ). Previous studies have found that BMSC-Exos can promote nerve function and improve the nervous system in ischemic stroke (Deng et al, 2019 ; Xiao et al, 2019 ; Hou et al, 2020 ; Safakheil and Safakheil, 2020 ), but the specific mechanism remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…As an important component of paracrine signaling in stem cells, exosomes appear to be promising candidates for repairing tissue injury in place of stem cells (Lazar et al, 2018 ; Williams et al, 2020 ). Previous studies have found that BMSC-Exos can promote nerve function and improve the nervous system in ischemic stroke (Deng et al, 2019 ; Xiao et al, 2019 ; Hou et al, 2020 ; Safakheil and Safakheil, 2020 ), but the specific mechanism remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…TJ protein expression in brain ECs at a relatively high level, can maintain the integrity of the BBB ( Zhang et al, 2020 ), which is crucial for brain homeostasis. In contrast, disruption of BBB integrity correlates with reduced expression of TJ proteins such as Occludin, Claudin-5, and ZO ( Nag et al, 2007 ; Williams et al, 2020 ). Mechanical stress associated with acute-stage TBI not only is detrimental to cells in the nervous system but also results in injury to the microvasculature in the brain, which consists of ECs, finally increasing paracellular permeability and causing a cascade of secondary damage to brain tissue ( Alvarez et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a Yorkshire swine model subjected to TBI and hemorrhagic shock, early single-dose administration (after one hour of shock) of MSC-exosomes contributed to relieving brain swelling, reducing lesion size, and maintaining BBB integrity. 131 Except for the early effects (6-hours), impact on late survival (7-days) was also observed -that is neurologic severity scores decrease significantly, accompanied by favorable neurologic recovery. 132…”
Section: Traumatic Brain Injury (Tbi) and Ichmentioning
confidence: 96%